Mechanical characterization of native and sugar-modified decellularized kidneys. (February 2021) - Sant, Snehal; Wang, Dan; Abidi, Minhal; Walker, Gwyneth; Ferrell, Nicholas
Abstract: Decellularized organs have the potential to be used as scaffolds for tissue engineering organ replacements. The mechanical properties of the extracellular matrix (ECM) following decellularization are critical for structural integrity and for regulation of cell function upon recellularization. Advanced glycation end products (AGEs) accumulate in the ECM with age and their formation is accelerated by several pathological conditions including diabetes. Some AGEs span multiple amino acids to form crosslinks that may alter the mechanical properties of the ECM. The goal of this work was to evaluate how sugar-induced modifications to the ECM affect the mechanical behavior of decellularized kidney. The compressive and tensile properties of the kidney ECM were evaluated using an accelerated model of AGE formation by ribose. Results show that ribose modifications significantly alter the mechanical behavior of decellularized kidney. Increased resistance to deformation corresponds to increased ECM crosslinking, and mechanical changes can be partially mitigated by AGE inhibition. The degree of post-translational modification of the ECM is dependent on the age and health of the organ donor and may play a role in regulating the mechanical properties of decellularized organs.